2015
DOI: 10.3390/molecules200712250
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Procyanidin B2 against CCl4-Induced Acute Liver Injury in Mice

Abstract: Procyanidin B2 has demonstrated several health benefits and medical properties. However, its protective effects against CCl4-induced hepatotoxicity have not been clarified. The present study aimed to investigate the hepatoprotective effects of procyanidin B2 in CCl4-treated mice. Our data showed that procyanidin B2 significantly decreased the CCl4-induced elevation of serum alanine aminotransferase activities, as well as improved hepatic histopathological abnormalities. Procyanidin B2 also significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 33 publications
9
77
0
1
Order By: Relevance
“…Also, CCl4 alter the antioxidant profile of the liver by reacting with sulfhydryl groups of glutathione (GSH) and thiols group of protein, including the antioxidant enzymes as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), and glutathione transferase (GST) (Knockaert et al, 2012;Yang et al, 2015).…”
Section: Epa Iris 2010)mentioning
confidence: 99%
“…Also, CCl4 alter the antioxidant profile of the liver by reacting with sulfhydryl groups of glutathione (GSH) and thiols group of protein, including the antioxidant enzymes as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), and glutathione transferase (GST) (Knockaert et al, 2012;Yang et al, 2015).…”
Section: Epa Iris 2010)mentioning
confidence: 99%
“…Later, the damage is through increased expression of various pro-inflammatory mediators such as tumor necrosis factor-α (TNF-α), transforming growth factor-β (TGF-β), interleukin-1 (IL-1), cyclooxygenase-2 (COX-2) and nuclear factor-κB (NF-κB). 15,16,17 When the liver cells are injured, its enzymes spill into the blood, causing elevated levels of ALT, AST, ALP, γ-glutamyl transpeptidase, sorbitol dehydrogenase, glutamate dehydrogenase and lactate dehydrogenase. Bilirubin, the endogenous product derived from the degradation of haemoglobin, builds up in the blood and extracellular fluid as its excretion is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is one of the main lipid peroxidation products, which was assessed as an indicator of lipid peroxidation in oxidative liver damage [63]. Saad et al [62] have reported a close relationship between lipid peroxidation and fibrogenesis in CCl 4 treated rats.…”
Section: Discussionmentioning
confidence: 99%